2021
DOI: 10.1016/j.aej.2021.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Prediction studies of the epidemic peak of coronavirus disease in Brazil via new generalised Caputo type fractional derivatives

Abstract: The first reported case of coronavirus disease (COVID-19) in Brazil was confirmed on 25 February 2020 and then the number of symptomatic cases produced day by day. In this manuscript, we studied the epidemic peaks of the novel coronavirus (COVID-19) in Brazil by the successful application of Predictor-Corrector (P-C) scheme. For the proposed model of COVID-19, the numerical solutions are performed by a model framework of the recent generalized Caputo type non-classical derivative. Existence of unique solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…A compartmental mathematical model was formulated to predict the evolution of the virus in Cameroon and to analyze the reported cases in Brazil [43,44]. The results achieved using these compartmental mathematical models indicated that the dynamics of COVID-19 disease are influenced by variations in the value of R 0 .…”
Section: Discussionmentioning
confidence: 99%
“…A compartmental mathematical model was formulated to predict the evolution of the virus in Cameroon and to analyze the reported cases in Brazil [43,44]. The results achieved using these compartmental mathematical models indicated that the dynamics of COVID-19 disease are influenced by variations in the value of R 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Several mathematical models have been devised to predict the epidemiologic trend of the COVID-19 outbreak, including stochastic/mathematical (integer derivative [15] , [16] or fractional-order [17] , [18] , [19] ) models, mass-action, (spatial) structured metapopulation, agent-based networked, and other compartmentalized models [20] , among others. According to a systematic survey of the literature, synthesizing 242 studies, 46.1% of studies used compartmental models, 31.8% statistical models (growth models and time series), 6.7%, 4.7%, 3.3%, 2.3% and 1.3% Artificial Intelligence-, Bayesian approach-, hybrid, network- and individual agent-based models, respectively [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists around the globe have done outstanding investigations on the transmission dynamics, forecasting, control tactics, and estimation for the infection of COVID-19. Several mathematicians have given the number of articles to define the structure of COVID-19, in which some are [1] , [2] , [3] , [4] , [5] , [6] , [7] . Ameen et al in [8] studied the structure of Coronavirus-19 with a fresh dynamical model.…”
Section: Introductionmentioning
confidence: 99%